Girl at sea - Johnson, Maureen, 1973- (New York : HarperTeen, 2008)
High-school junior Clio Ford reluctantly gives up her dream job and a potential first kiss to take a working vacation with her estranged father on a yacht in Italy.
Booklist.
Publisher's Weekly.
School Library Journal.
Young Adult
Keywords: Archaeology -- Juvenile fiction; Artists -- Juvenile fiction; Boats and boating -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Archaeology -- Fiction; Artists -- Fiction; Boats and boating -- Fiction; Fathers and daughters -- Fiction; Interpersonal relations -- Fiction; Archeology -- Fiction; Artists -- Fiction; Boats and boating -- Fiction; Father-daughter relationship -- Fiction; Interpersonal relations -- Fiction; Italy -- Juvenile fiction; Italy -- Fiction; Italy -- Fiction